2020
DOI: 10.1002/anie.202001205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Histone deacetylase (HDAC)‐Associated Proteins with DNA‐Programmed Affinity Labeling

Abstract: Histone deacetylase (HDAC) is a major class of deacetylation enzymes. Many HDACs exist in large protein complexes in cells and their functions strongly depend on the complex composition. The identification of HDAC‐associated proteins is highly important in understanding their molecular mechanisms. Although affinity probes have been developed to study HDACs, they were mostly targeting the direct binder HDAC, while other proteins in the complex remain underexplored. We report a DNA‐based affinity labeling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 72 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Moreover, a single BP can be paired with multiple CPs at different positions to create multiple probe configurations to maximize labeling coverage. This feature has been recently used to profile large protein complexes in cell lysates . Finally, DNA-based probes can be multiplexed to interrogate multiple proteins simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a single BP can be paired with multiple CPs at different positions to create multiple probe configurations to maximize labeling coverage. This feature has been recently used to profile large protein complexes in cell lysates . Finally, DNA-based probes can be multiplexed to interrogate multiple proteins simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the DNA tag was delivered using a DNA-programmed affinity labelling (DPAL) method previously developed for protein profiling and target identification. [75,88] This study showed that small molecules and antibodies could be used for tag delivery. Other types of ligands that have been used to graft DNAs on cells, such as peptides, [89] small-engineered proteins, [90] and aptamers, [91] may also be used to expand the target scope.…”
Section: Selection Against Membrane Proteinsmentioning
confidence: 95%
“…Recently, Li and co-workers reported a DNAprogrammed affinity labelling (DPAL) of histone deacetylase (HDAC) complexes, suggesting the possibility of DEL selection against endogenous protein complexes in cell lysates without purification and immobilization. [75]…”
Section: Selection In Cell Lysates and With Protein Complexesmentioning
confidence: 99%
See 2 more Smart Citations